Analisis Didaktik Penggunaan Gadget dan Relevansinya pada Motivasi Belajar Siswa dengan Pendekatan Appreciative Inquiry - Pangalingan, Noviyanti (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
The use of technology in the teaching and learning process can increase the effectiveness and efficiency of learning. However, there are still many schools that are not optimal in integrating technology in the teaching and learning process. This is due to several factors, such as limited infrastructure, lack of teachers' ability to use technology, and lack of support from schools and parents This study aims to analyze the use of gadgets and their relevance to the learning motives of students at SMP Negeri 3 Makassar with an Appreciative Inquiry approach. The research method used in this study is a qualitative method with a phenomenological approach, which is a research method that focuses on the subjective experience of individuals or groups.  The results of the study show that the use of gadgets in learning is a special attraction that breaks the enthusiasm of students in participating in the teaching and learning process. The learning approach seeks to promote deep understanding. The use of gadgets at UPT SPF SMP 3 Makassar has a positive impact on student learning achievement. In addition to making students more knowledgeable, the use of gadgets also has a social impact on students, by accessing the internet students can first know the problems that occur and provide participation in the form of support. The presence of gadgets makes students more insightful, student learning outcomes improve well after using gadgets. The achievements achieved by students are not only academic achievements but many achievements obtained, for example, students use technological tools to make money through social media.